Cultivating professional resilience in direct practice : a guide for human service professionals - Newell, Jason M. (Columbia University Press, 2017)
Overwhelming evidence indicates that new social workers going into child welfare or other trauma-related care discover emotional challenges. In a textbook that bridges the gap between theoretical and pragmatic approaches, Jason M. Newell provides a solution by conceptualizing self-care as the key to professional resilience.